Apparent bias for P. falciparum parasites carrying the wild-type pfcrt allele in the placenta - Oster, Nadja; Rohrbach, Petra; Sanchez, Cecilia P.; Andrews, Katharine T.; Kammer, Judith; Coulibaly, Boubacar; Stieglbauer, Gabriele; Becher, Heiko; Lanzer, Michael (Parasitology research, 2010)
Resistance to chloroquine has been linked to polymorphisms within the pfcrt gene of the human malarial parasite Plasmodium falciparum. Here, we have investigated the prevalence of the pfcrt allele associated with chloroquine resistance in the peripheral blood and the placenta of pregnant women diagnosed with a P. falciparum infection. Our molecular epidemiological data show an unequal distribution with a significant under-representation of parasites carrying the mutated pfcrt allele in the placenta, as compared to the peripheral blood. In comparison, no differences were seen with regard to pfmdr1 polymorphisms of these parasites. Our data suggest a selective disadvantage of the polymorphic and a selective advantage of the wild-type pfcrt haplotype in the placenta, supporting the model that the human host provides various microenvironments that favor genetically distinct P. falciparum populations.
Gesehen am 19.06.2023